Advanced provision of emergency contraception does not reduce abortion rates. - Glasier, A; Fairhurst, K; Wyke, S; Ziebland, S; Seaman, P; Walker, J; Lakha, F (2004)
A number of small studies have demonstrated increased use of emergency contraception (EC) when women have a supply available at home. It has been suggested that widespread use of EC could reduce abortion rates. We undertook a community intervention study designed to determine whether offering advanced supplies of EC to large numbers of women influenced abortion rates. All women aged between 16 and 29 years living in Lothian, Scotland, were offered, through health services, five courses of EC without cost to keep at home. Of a population of around 85,000 women in this age group, the study showed that an estimated 17,800 women took a supply of EC home and over 4500 of them gave at least one course to a friend. It was found that nearly half (45%) of women who had a supply used at least one course during the 28 months that the study lasted. In total, an estimated 8081 courses of EC were used. EC was used within 24 h after intercourse on 75% of occasions. Abortion rates in Lothian were compared with those from three other health board areas of Scotland. No effect on abortion rates was demonstrated with advanced provision of EC. The results of this study suggest that widespread distribution of advanced supplies of EC through health services may not be an effective way to reduce the incidence of unintended pregnancy in the UK.